Smart Logistics Integration: 5G Networks and IoT Technologies in Modern Supply Chain Management - Tamara Saad Mohamed (Academic International Journal of Engineering Science, 2025)
The combination of 5G and internet of things IoT technology is fundamentally a game-changer in smart logistics. This paper will consider the impact of 5G-enabled IoT networks on the entire supply chain, examining innovative network designs such as network slicing, multi-access edge computing (MEC), and low-power wide-area networks (LPWAN). In essence, the paper demonstrating that such technologies can increase warehouse efficiency by 20% and that the use of solutions rooted in narrowband IoT (NB-IoT) may help increase yard dispatch efficiency by 87%.Our systematic digital twin simulations and real-world tests have shown that bespoke network slices and edge computing are highly effective in meeting numerous logistics requirements. They improve throughput, strip off latency and enhance reliability. The paper provides specific, concrete information that IT professionals, telecom engineers, and supply-chain managers can apply in practice when implementing next-generation logistics solutions.
Keywords: Smart logistics, 5G, Internet of Things, supply chain management, network slicing, edge computing.